Glomerular hyperfiltration is a predictor of adverse cardiovascular outcomes - Reboldi, Gianpaolo; Verdecchia, Paolo; Fiorucci, Gioia; Beilin, Lawrence J; Eguchi, Kazuo; Imai, Yutaka; Kario, Kazuomi; Ohkubo, Takayoshi; Pierdomenico, Sante D; Schwartz, Joseph E; Wing, Lindon; Saladini, Francesca; et al. (Kidney international, 2018)
The association between glomerular hyperfiltration and cardiovascular events is not well known. To investigate whether glomerular hyperfiltration is independently associated with risk of adverse outcome we analyzed 8794 participants, average age 52 years enrolled in 8 prospective studies. Of these, 89% had hypertension. Using the 5th and 95th percentiles of the age- and sex-specific quintiles of CKD-EPI-calculated estimated glomerular filtration rate (eGFR), we identified three participant groups with low, high and normal eGFR. The ambulatory pulse pressure interval was wider and nighttime blood pressure fall was smaller in both the low and high than in the normal eGFR participants. During a mean follow-up of 6.2 years, there were 722 cardiovascular events. Crude event rates were significantly higher for both high (1.8 per 100-person-year) and low eGFR groups (2.1 per 100 person-year) as compared with group with normal eGFR (1.2 per 100 person-year). In multivariable Cox models including age, sex, average 24-hour blood pressure, smoking, diabetes, and cholesterol, both high eGFR (hazard ratio 1.5 (95% confidence interval 1.2-2.1) and low eGFR (2.0 [1.5-2.6]) participants had a significantly higher risk of cardiovascular events as compared to those with normal eGFR. Addition of body mass index to the multivariable survival model did not change the magnitude of hazard estimates. Thus, glomerular hyperfiltration is a strong and independent predictor of cardiovascular events in a large multiethnic population of predominantly hypertensive individuals. Our findings support a U-shaped relationship between eGFR and adverse outcome.